PRINSIP LOSS LEADER (HARGA UMPAN) ATAS PENJUALAN PRODUK CUCI GUDANG PADA PUSAT PERBELANJAAN RAMAYANA ROBINSON PEKANBARU - Silaban, Adi Putra; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The intense competition in the retail business makes some business players justify any means, which in turn makes the climate of unfair competition. Sales of warehouse washing products, no longer just reduce the percentage of profits from the selling price of the product, but have arrived at the stage of selling even or even have a sale with a little loss. The purpose of this study, first is to find out how legal protection to consumers for the sale of warehouse washing products based on the principle of loss leader. And secondly, to find out the business actors' responsibility for consumer losses on the sale of warehouse washing products based on the principle of loss leader.In this study the author uses the empirical method, another term used is sociological. The study of the effectiveness of the laws that apply in society and identify unwritten laws that apply in the community. In this case the researchers conducted a study on the shopping center Ramayana Robinson Panam Kota Peknabaru. In data collection, the types of data used in this study are primary data and secondary data, namely directly through respondents (field), Law Number 8 of 1999 concerning Consumer Protection, legal journals and books relating to research. Analysis of this data is done qualitatively and deductively drawn conclusions.From the results of the research in this thesis, there are two main things that are concluded, namely First, legal protection for consumers on the sale of warehouse products based on the principle of loss leader. And second, the form of businessactors responsibility for Consumer losses on the sale of warehouse washing products based on the principle of loss leader.Keywords: Consumer - Responsibility - Business actor - Consumer Protection